The evolution of paternal care can lead to population growth in artificial societies. (7th September 2015) - Salgado, Mauricio
Abstract: Evolutionary models of paternal care predict that when female reproductive effort is higher than male reproductive effort, selection might favour the emergence of unconditional male cooperation towards females, even when the latter group does not reciprocate. However, previous models have assumed constant population sizes, so the ecology of interacting individuals and its effects on population dynamics have been neglected. This paper reports an agent-based model that incorporates ecological dynamics into evolutionary game dynamics by allowing populations to vary. As previous models demonstrate, paternal care only evolves when female reproductive effort is higher than that of males, and the optimal strategy for females is to exploit male unconditional cooperation. The model also shows that evolution of this behaviour drives some simulations towards regimes of population growth. Thanks to the evolution of paternal care, females׳ inter-birth intervals are shortened and causing them to reproduce faster. Thus, it is suggested that the evolution of paternal care in species with differential reproductive effort between sexes could be associated to population growth. Nevertheless, the modelled evolutionary dynamics are stochastic, so differences in reproductive effort are necessary but not sufficient conditions for the evolution of paternal care. Highlights: An agent-based model that relates paternal care and population dynamics is reported. Females elicit and exploit paternal care when their reproductive costs are high. Females reproduce faster and populations grow when paternal care is selected. Majority of simulations go extinct regardless of differences in reproductive costs. Sex-based differences in reproductive costs are not enough to produce paternal care.